2008
DOI: 10.1111/j.1462-5822.2008.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliinteraction with human brain microvascular endothelial cells induces signal transducer and activator of transcription 3 association with the C-terminal domain of Ec-gp96, the outer membrane protein A receptor for invasion

Abstract: SummaryOur inability to develop new therapeutic strategies to prevent meningitis due to Escherichia coli K1 is attributed to our incomplete understanding of the pathophysiology of the disease. Previously, we demonstrated that outer membrane protein A of E. coli interacts with a gp96 homologue, Ec-gp96, on human brain microvascular endothelial cells (HBMEC) for invasion. However, signalling events mediated by Ec-gp96 that allow internalization of E. coli are incompletely understood. Here, we demonstrate that si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…OmpA interacts with the N terminus of Gp96 at the surface of human brain microvascular endothelial cells to promote infection (38). Here we show that despite the lack of homology shared between OmpA and Vip the listerial protein also interacts with the N terminus of Gp96.…”
Section: Discussionmentioning
confidence: 78%
“…OmpA interacts with the N terminus of Gp96 at the surface of human brain microvascular endothelial cells to promote infection (38). Here we show that despite the lack of homology shared between OmpA and Vip the listerial protein also interacts with the N terminus of Gp96.…”
Section: Discussionmentioning
confidence: 78%
“…The two 90-kDa heat shock proteins of human cells, Hsp90 and gp96, are increasingly seen to play important roles in bacterial virulence and may open up new therapeutic avenues. The role of these proteins was first discovered when it was found that gp96 on the outer surface of (122), and the levels of Ec-gp96 are controlled by nitric oxide/cGMP signaling (125). gp96 is an endoplasmic reticulum (ER) Hsp90 family member, and evidence has recently been found for its role in the uptake of bacterial toxins.…”
Section: Bacterial Molecular Chaperones and Protein-folding Catalystsmentioning
confidence: 99%
“…Recently, STAT3 was found to interact with Cav-1 and heat shock protein 90 in plasma membrane rafts during Escherichia coli infection (26). Cav-1 is also related to a JAK2/STAT5 pathway because Cav-1 is homologous to the pseudosubstrate for SOCS.…”
mentioning
confidence: 99%